Porous flower-like superstructures based on self-assembled colloidal quantum dots for sensing - Gounko, Iouri (My University, 2019)
Quantum dots (QDs) have been envisaged as very promising materials for the development of advanced optical sensors. Here we report a new highly porous luminescent material based on colloidal QDs for potential applications in optical sensing devices. Bulk flower-like porous structures with sizes of hundreds of microns have been produced by slow destabilization of QD solution in the presence of a non-solvent vapor. The porous highly luminescent material was formed from CdSe QDs using the approach of non-solvent destabilization. This material demonstrated a 4-fold decrease in PL signal in the presence of the ammonia vapor. The relationship between the destabilization rate of QDs in solution and the resulting morphology of structural elements has been established. The proposed model of bulk porous flower-like nanostructured material fabrication can be applied to nanoparticles of different nature combining their unique properties. This research opens up a new approach to design novel multi-component composite materials enabling potential performance improvements of various photonic devices.
Sci Rep
PUBLISHED
Keywords: photonic device; Quantum dots (QDs); optical sensors